THE PROBLEM OF FREQUENTLY ILL CHILDREN IN EARLY CHILDHOOD: CAUSES, RISK FACTORS, AND PREVENTIVE MEASURES (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article analyzes the relevance of the problem of frequent morbidity in early childhood, as well as its main etiological causes and the biological, social, and hygienic risk factors influencing its development, based on a review of scientific literature. The predominance of acute respiratory infections among frequently ill children (FIC), immune system immaturity, perinatal pathologies, improper nutrition, psychoemotional stress, and environmental factors are highlighted. In addition, primary, secondary, and socio-hygienic preventive measures aimed at disease prevention and health promotion in this group of children are examined. The obtained data demonstrate the necessity of addressing frequent morbidity through a comprehensive and integrated approach.
Keywords: Frequently ill children, early childhood, respiratory infections, immunity, risk factors, prevention.